If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 7) = 26 Reorder the terms: 3(7 + x) = 26 (7 * 3 + x * 3) = 26 (21 + 3x) = 26 Solving 21 + 3x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 3x = 26 + -21 Combine like terms: 21 + -21 = 0 0 + 3x = 26 + -21 3x = 26 + -21 Combine like terms: 26 + -21 = 5 3x = 5 Divide each side by '3'. x = 1.666666667 Simplifying x = 1.666666667
| 55=39-5c | | 4x(3x-1)= | | 3(5c-1)=4(3c+2) | | 4v^2=-11v-6 | | 6n-2=4n+6 | | 3x(x+5)= | | 2x^2-20x=-42 | | y+5+2y= | | 6x+5x=63 | | 4(n-1)=-8 | | y^2+9y=-20 | | 5y-2(y+4)=1 | | 3x^2-8x^7-2x^2=9x^7 | | 6x^2-8x-12=0 | | 2K(K+3)=-9 | | 2K(K+3)=9 | | 3(x-4)+15=2(x+3) | | 6y^2-6=0 | | 5/12-7/8= | | 4x^2=4x | | -1/5-4(m+1/12)=39/10(m-11/6) | | a^2b^2-121=0 | | 9+-10x+x^4=0 | | x+6x-40=0 | | -10x+3+9x=-x-7 | | x^4-10x+9=0 | | 5v^3-65v^2+200v=0 | | 2x-7/3=-7 | | 8a+a= | | 6a+12=2a-6 | | 8a-3b+2a+6b= | | 3y+5y=9y |